Faktor Yang Berhubungan Dengan Kepatuhan Minum Obat Pada Penderita Skizofrenia Fase Stabil Di Poli Rawat Jalan RS Jiwa Daerah Provinsi Lampung Tahun 2022 - Harissa, Nola; Anggriani, Yusi; Sarnianto, Prih; Septa, Tendry (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2023)
Adherence with antipsychotic treatment is very important to achieve optimal therapeutic results to the people with schizophrenia. The aim of the study is to determine the factors associated with medication adherence in patients with stable phase of paranoid schizophrenia at the Outpatient Polyclinic of the Regional Hospital of Lampung Province in 2022. This study used a crosssectional method with prospective data collection, a sample of 176 and the use of purposive sampling for the sampling technique. The data obtained were analyzed by using the chi square test to find out the relation between the dependent variable which is medication adherence, and the independent variables, namely perceptions of family support, knowledge related to disease, perceptions of drug side effects, and the perceptions of the pharmacist's role. To find out the dominant factors influencing the medicine compliance, the data were analyzed by using ordinal logistic regression. The study obtained of medicine compliance rates in paranoid schizophrenia patients based on the MMAS scale were good in 53 (30.1%), moderate in 62 (35.2%) and poor in 61 (34.7%). There is a relationship between medication adherence and the perception of family support (p value 0.038), knowledge related to disease (p value 0.005), perception of drug side effects (p value 0.003), and perception of the role of pharmacist (p value 0.000). The dominant factor affecting compliance to taking medication is the perception of the pharmacist's role with OR = 2.8, which means patients who get a good pharmacist role are more compliant in taking medication by 2.8 times. Keywords: Medication Compliance, Paranoid Schizophrenia, Stable Phase, Outpatient